Estudo da dispersão e concentração de minério calamínico - Carlos Alberto Pereira (2004)
Brazil holds one of the few world reserves of calamine ore. The technological development for processing this ore occurred after the second world war and until the seventies Italy and France lead the investigations on this subject. after the depletion of their reserves research work on this field slowed down. The demand for zinc in Brazil isincreasing steadily. In order to reduce the production deficit, this laboratory scale investigation aims at contributing to enhance zinc recovery by means of a more effective dispersion and the use of alternative reagents for the flotation of calamine ore slimes. The dispersion of the mineral particles in the pulp is crucial for increasing theflotation selectivity of these ores. The present investigation included characterization, dispersion and flotation studies. The characterization stage showed that the calamine ore presents specific surface area three times larger than the willemite ore. X-ray diffraction detected the minor presence of other zinc bearing minerals. Statistic tools of two levelsreplicate complete factorial design and optimization by means of the ascending path method. These tools rendered it feasible to evaluate the interactions among several variables: dispersing agents, sodium sulfide, pH, and reagents addition sequence. Calgon, sodiumhexametaphosphate, sodium polyacrylate (dispersol 589) andcarboxymethyl cellulose (CMC) were used as dispersants. The results showed that the best level of dispersion of the particles in pulp was achieved with sodium hexametaphosphate. The best sodium sulfide : sodium carbonate ratio, required for sulfidization, was defined in the flotation stage. Regarding flotation reagents, the amine/fuel oil/MIBC emulsion at the 1:0.16:0.4 rendered the flotation feasible for pH values lower than 11.5. Flotation with Genamin, a coconut amine, could be performed in the less alkaline pH range. Sodium silicate was effective in flotation either as dispersant or as dolomite depressant. A high dosage of 3000g/t is required. Magnetic separation, previous to flotation, increased zinc recovery and grade in the concentrate. The zero charge condition of hemimorphite was determined by the Mular & Roberts method at pH 7, confirming the results achieved in the dispersion studies.